2016
DOI: 10.1371/journal.pone.0157062
|View full text |Cite
|
Sign up to set email alerts
|

Increased Uptake of HCV Testing through a Community-Based Educational Intervention in Difficult-to-Reach People Who Inject Drugs: Results from the ANRS-AERLI Study

Abstract: AimsThe community-based AERLI intervention provided training and education to people who inject drugs (PWID) about HIV and HCV transmission risk reduction, with a focus on drug injecting practices, other injection-related complications, and access to HIV and HCV testing and care. We hypothesized that in such a population where HCV prevalence is very high and where few know their HCV serostatus, AERLI would lead to increased HCV testing.MethodsThe national multisite intervention study ANRS-AERLI consisted in as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Among 10,116 records identified, a total of 14 studies were included, of which 57% were randomised controlled trials. Interventions to enhance HCV testing included on-site testing with pre-test counselling and education (Cullen, et al, 2006;Hagedorn, et al, 2007;Lacey, Ellen, Devlin, Wright, & Mijch, 2007;Merchant, et al, 2014;Merchant, DeLong, Liu, & Baird, 2015;Rosenberg, et al, 2010;Roux, et al, 2016); and dried blood spot testing (Hickman, et al, 2008;Radley, et al, 2017). Interventions to enhance linkage to care included facilitated referral for HCV assessment and scheduling of specialist appointments for clients (Cullen, et al, 2006;Masson, et al, 2013;Tait, McIntyre, McLeod, Nathwani, & Dillon, 2010).…”
Section: Enhancing Testing Linkage To Care and Treatment For Pwidmentioning
confidence: 99%
“…Among 10,116 records identified, a total of 14 studies were included, of which 57% were randomised controlled trials. Interventions to enhance HCV testing included on-site testing with pre-test counselling and education (Cullen, et al, 2006;Hagedorn, et al, 2007;Lacey, Ellen, Devlin, Wright, & Mijch, 2007;Merchant, et al, 2014;Merchant, DeLong, Liu, & Baird, 2015;Rosenberg, et al, 2010;Roux, et al, 2016); and dried blood spot testing (Hickman, et al, 2008;Radley, et al, 2017). Interventions to enhance linkage to care included facilitated referral for HCV assessment and scheduling of specialist appointments for clients (Cullen, et al, 2006;Masson, et al, 2013;Tait, McIntyre, McLeod, Nathwani, & Dillon, 2010).…”
Section: Enhancing Testing Linkage To Care and Treatment For Pwidmentioning
confidence: 99%
“…One such existing intervention, called AERLI, was community-based and focused on reducing injection-related harm. Conducted by peers and other health staff, it was based on two nested phases: the use of a standardized checklist when supervising injection and a tailored intervention to reduce harm which included information about hepatitis C testing and treatment.The ANRS AERLI study showed a significant reduction in HCV risk practices and an increase in HCV testing in the intervention group [4,5]. The importance of these results led AERLI to be included as a novel prevention intervention in the new 2016 French health law.…”
mentioning
confidence: 99%
“…The ANRS AERLI study showed a significant reduction in HCV risk practices and an increase in HCV testing in the intervention group [4,5]. The importance of these results led AERLI to be included as a novel prevention intervention in the new 2016 French health law.…”
mentioning
confidence: 99%
See 2 more Smart Citations